The effects of a multi-tiered system of language support on oral narrative language, writing, and reading comprehension in India. (2nd January 2022) - Nelson, Brenna Scadden; Petersen, Douglas B.; Rai, Anuradha
Abstract: Background: Children in India are among the lowest performing students on international reading comprehension and writing assessments. Oral language instruction may improve these literacy outcomes. Aim: This pilot study investigated whether a multi-tiered system of language support (MTSLS) improved oral narrative language comprehension, reading comprehension, and writing in second and third grade students in India. Methods & Procedures: There were 121 second and third grade participants in this quasi-experimental study. Twelve classrooms were randomly assigned to a treatment, an alternate-treatment, or a no-treatment control condition. The treatment group participated in 8 weeks of multi-tiered Story Champs oral language intervention, the alternate-treatment group participated in 8 weeks of shared storybook intervention, and the no-treatment group served as a control. Teachers in India received training and feedback from researchers in the U.S. using videoconferencing. Videoconferencing was also used to deliver the small group, tier-2 Story Champs intervention. Results: Results indicated that students who received Story Champs instruction had significantly higher scores across all outcomes compared to the students in the alternate-treatment and in the no-treatment control groups. Conclusions: This pilot study indicates that oral narrative MTSLS instruction may help students in India improve their oral language, reading comprehension, and writing performance.